Last visit was: 16 Jun 2024, 23:24 It is currently 16 Jun 2024, 23:24
Close
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Close
Request Expert Reply
Confirm Cancel
SORT BY:
Date
Math Expert
Joined: 02 Sep 2009
Posts: 93698
Own Kudos [?]: 632357 [7]
Given Kudos: 82304
Send PM
Most Helpful Reply
GMAT Club Legend
GMAT Club Legend
Joined: 12 Sep 2015
Posts: 6814
Own Kudos [?]: 30567 [6]
Given Kudos: 799
Location: Canada
Send PM
General Discussion
Director
Director
Joined: 25 Oct 2015
Posts: 516
Own Kudos [?]: 886 [1]
Given Kudos: 74
Location: India
GMAT 1: 650 Q48 V31
GMAT 2: 720 Q49 V38 (Online)
GPA: 4
Send PM
Senior Manager
Senior Manager
Joined: 14 Oct 2019
Status:Today a Reader; Tomorrow a Leader.
Posts: 346
Own Kudos [?]: 356 [0]
Given Kudos: 127
Location: India
GPA: 4
WE:Engineering (Energy and Utilities)
Send PM
Re: If f(x + 2) = f(x) + f(x + 1) for all positive integers x, and f(11) = [#permalink]
Given , f(x + 2) = f(x) + f(x + 1)
f(15) = f(13) + f(14)
f(13) + f(14) = 617 —————1)
f(12) + f(13) = f(14) ————-2)
f(11) + f(12) = f(13)————-3)
from eq 1) , 2) & 3)
2f(11) + 3f(12) = 617
Putting f(11) = 91
f(12) = (617 – 2*91)/3 = 145
f(12) = f(11) + f(10)
so f(10) = f(12) – f(11) = 145 – 91 =54
Answer: B
SVP
SVP
Joined: 24 Nov 2016
Posts: 1714
Own Kudos [?]: 1352 [1]
Given Kudos: 607
Location: United States
Send PM
Re: If f(x + 2) = f(x) + f(x + 1) for all positive integers x, and f(11) = [#permalink]
1
Kudos
Bunuel wrote:
If \(f(x + 2) = f(x) + f(x + 1)\) for all positive integers x, and \(f(11) = 91\), \(f(15) = 617\), then what is the value of \(f(10)\) ?

A. 53
B. 54
C. 55
D. 56
E. 57


617=f14+f13=f13+f12+f13=2(f13)+f12=2(f12+f11)+f12
617=3f12+91, f12=435/3=145, f12=f11+f10
145=91+f10, f10=54

ans (B)
Tutor
Joined: 05 Apr 2011
Status:Tutor - BrushMyQuant
Posts: 1787
Own Kudos [?]: 2121 [1]
Given Kudos: 100
Location: India
Concentration: Finance, Marketing
Schools: XLRI (A)
GMAT 1: 700 Q51 V31
GPA: 3
WE:Information Technology (Computer Software)
Send PM
Re: If f(x + 2) = f(x) + f(x + 1) for all positive integers x, and f(11) = [#permalink]
1
Kudos
Expert Reply
Top Contributor
Given that \(f(x + 2) = f(x) + f(x + 1)\) for all positive integers x , and \(f(11) = 91\), \(f(15) = 617\) and we need to find the value of \(f(10)\)

\(f(x + 2) = f(x) + f(x + 1)\) - this means that f(any positive integer) = sum of f of previous two numbers
=> f(15) = f(13) + f(14) ...(1)
f(14) = f(12) + f(13) ...(2)
f(13) = f(11) + f(12) ....(3)
f(12) = f(10) + f(11)

Putting value of f(12) in (3) we get
f(13) = f(11) + f(10) + f(11) = f(10) + 2*f(11)

Putting value of f(13) and f(12) in (2) we get
f(14) = f(10) + f(11) + f(10) + 2*f(11) = 2*f(10) + 3*f(11)

Putting value of f(14) and f(13) in (1) we get
f(15) = f(10) + 2*f(11) + 2*f(10) + 3*f(11) = 3*f(10) + 5*f(11)
=> f(10) = \(\frac{f(15) - 5*f(11) }{3}\) = \(\frac{617 - 5*91}{3}\) = \(\frac{617-455}{3}\) = \(\frac{162}{3}\) = 54

So, Answer will be B
Hope it helps!

Watch the following video to learn the Basics of Functions and Custom Characters

GMAT Club Bot
Re: If f(x + 2) = f(x) + f(x + 1) for all positive integers x, and f(11) = [#permalink]
Moderator:
Math Expert
93698 posts